From theory to experiment: hadron electromagnetic form factors in space-like and time-like regions - Tomasi-Gustafsson, E.; Gakh, G.I.; Rekalo, A.P. (Вопросы атомной науки и техники, 2007)
Hadron electromagnetic form factors contain information on the intrinsic structure of the hadrons. The pioneering work developed at the Kharkov Physical-Technical Institute in the 60's on the relation between the polarized cross section and the proton form factors triggered a number of experiments. Such experiments could be performed only recently, due to the progress in accelerator and polarimetry techniques. The principle of these measurements is recalled and surprise and very precise results obtained on proton are presented. The actual status of nucleon electromagnetic form factors is reviewed, with special attention to the basic work done in Kharkov Physical-Technical Institute. This paper is devoted to the memory of Prof. M.P. Rekalo. Електромагнітні формфактори адронів містять інформацію про внутрішню структуру адронів. Піонерська робота, виконана у 60-ті роки у Харківському фізико-технічному інституті, яка була присвячена зв’язку протонних формфакторів з перерізом розсіювання поляризованих частинок, ініціювала низку експериментів. Такі експерименти стали можливими зовсім недавно завдяки прогресу у конструюванні прискорювачів та поляриметрів. Наведені умови цих вимірювань та прецизійні результати дослідів з протонами. Представлений сучасний стан електромагнітних формфакторів нуклонів, особлива увага приділена основоположній роботі, яка була виконана у Харківському фізико-технічному інституті. Стаття присвячена пам’яті професора М.П. Рекала. Электромагнитные формфакторы адронов содержат информацию о внутренней структуре адронов. Пионерская работа, выполненная в 60-е годы в Харьковском физико-техническом институте, посвященная связи протонных формфакторов с сечением рассеяния поляризованных частиц, инициировала ряд экспериментов. Такие эксперименты стали возможны совсем недавно благодаря прогрессу в конструировании ускорителей и поляриметров. Приведены условия этих измерений и прецизионные результаты опытов с протонами. Представлен современный статус электромагнитных формфакторов нуклонов, особое внимание уделено основополагающей работе, выполненной в Харьковском физико-техническом институте. Статья посвящена памяти профессора М.П. Рекало.